Investigation of non-prostatic in vitro prostate-specific membrane antigen expression in MCF-7 and MDA-MB-231 breast tumour cells - Cromarty, Allan Duncan (University of Pretoria, 2021)
Dissertation (MSc)--University of Pretoria, 2020.